Pre-service students’ experiences at Teacher Training Programmes during the Covid-19 pandemic: what teacher trainers should know - Ianiro, María Eugenia; Ojeda, Sandra Guadalupe (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The world has been undergoing one of the most dramatic changes ever experienced by humanity due to COVID-19 pandemic. Consequently, teachers have adapted to this unforeseen situation, trying to tackle the new outbreaking challenges. Being English as Foreign Language Teachers (EFL), we carried out a survey to obtain data about students’ experiences in the context of emergency remote teaching (ERT). As a result, an online questionnaire was given to students from four different EFL teacher training programmes in three provinces of Argentina at the end of the first semester in 2020. The information included in this article might shed light upon trainees' perspectives and give higher education teachers the possibility to reflect on their academic and pedagogical practices.